ANALISIS PENERIMAAN RAIL TICKET SYSTEM PADA PT. KAI DENGAN MENGGUNAKAN MODEL UTAUT - Yesni Malau (Paradigma, 2016)
Rail ticket system is a train ticket booking system online that have been implemented by PT.KAI. To find out how far the success rate of acceptance of rail ticket system for the users of transport services, PT.KAI needs to test the rail ticket system. Tests conducted to determine the factors that influence user acceptance rail ticket system. Testing model in this study is using a model of the Unified Theory of Acceptance and Use of Technology (UTAUT), this model to analyze the influence of performance expectancy (expectation of performance), effort expectancy (expectation of business) and social influence (social factors) on behavioral intention (intention utilization) and the effect of facilitating conditions (conditions that facilitate) and behavioral intention (intention utilization) to use behavior (behavioral usage) on a rail ticket system. Based on this study will be known factors that influence the behavioral intention and use behavior and the factors that do not affect the behavioral intention. With the research is expected to provide recommendations were appropriate and beneficial for PT. KAI in developing online train ticket booking system in the future. Based on the obtained data processed Fvalues of 5.175 and 3.09 Ftable this means Fvalues> Ftable with a significant level of 0,000 F below 0.05 that is jointly independent variable performance expectancy, effort expectancy and social influence significantly influence the dependent variable behavioral intention. The amount of independent influence performance expectancy, effort expectancy and social influence views on the value of R square of 0.139 Retrieved value Fvalues 8.303 and Ftable by 3.94 this means Fvalues> Ftable with a significant level of 0.000 is below 0.05, it indicates that is jointly variable Facilitating Conditions and Behavioral Intention significantly affect Behavior Use variables, the influence of the independent performance expectancy, effort expectancy and social influence can be seen where the value of R square of 0.146. With this research is expected to provide recommendations which are appropriate and beneficial for PT. KAI in developing online train ticket booking system in the future.Key Words : Rail ticket system, UTAUT, SPSS